핵폐기용 모의글라스의 조성변화에 따른 용출특성에 관한 연구 - 한호현(H. H. Han); 이승한(S. H. Lee); 류수착(S. C. Ryu); 류봉기(B. K. Ryu) (Biuletyn Uniejowski, 1995)
In order to manufacture an attractive waste glass for the permanent and secure disposal of high-level radioactive waste, the complex composition of the simulated nuclear waste glass PNL-7668 was simplified to a composition of sodium borosilicate glass. The substitutions of $Fe_2O_3$ and $Al_2O_3$ were added to examine on the leaching characteristics of simulated nuclear waste glass with variable composition. The leach tests for these glasses were performed according to 'MCC-1, Static Leach Test Procedure' in acid and basic solution. In this study, for the $Al_2O_3$-containing glasses, Na ion release from these glasses was higher in acid solution than in basic solution. As the content of $Fe_2O_3$ was increased in glasses, Na ion release was increased in acid solution, in spite of decrease of amount of total mass diminution.